2020
DOI: 10.21037/atm-20-7201
|View full text |Cite
|
Sign up to set email alerts
|

Neferine induces p38 MAPK/JNK1/2 activation to modulate melanoma proliferation, apoptosis, and oxidative stress

Abstract: Background: Melanoma is a malignant skin cancer that has a poor prognosis in advanced patients. The aim of the present study was to investigate the antitumor role of neferine in melanoma.Methods: A375 and C32 cells were selected as research vectors in vitro. Cell counting Kit-8, 5-ethynyl-2'deoxyuridine staining, transwell, and flow cytometry assay were used to examined cell malignant phenotypes. Mitochondrial dysfunction was detected by 5,50,6,60-tetrachloro-1,10,3,30-tetraethyl-imidacarbocyanine iodide stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Oxidative stress affects cell proliferation via various signaling pathways, including EGFR and mTOR pathways that involve key signaling proteins like Ras, Raf, and MAPK pathway factors like ERK1/2, MEK, and p38 ( 25 , 26 ). p38 is a key sensor for oxidative stress, and its redox-sensing function is essential for controlling tumor development ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress affects cell proliferation via various signaling pathways, including EGFR and mTOR pathways that involve key signaling proteins like Ras, Raf, and MAPK pathway factors like ERK1/2, MEK, and p38 ( 25 , 26 ). p38 is a key sensor for oxidative stress, and its redox-sensing function is essential for controlling tumor development ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neferine comes from the lotus core (the embryo of the seed) of the plant Nelumbo nucifera and is a major bisbenzylisoquinoline alkaloid. There is evidence that neferine has a wide range of pharmacological properties, such as anti-cancer, anti-oxidant, antiinflammatory, and neuroprotective effects, in many diseases [10][11][12][13][14][15]. Khan et al found that neferine produces anti-photoaging effects by inhibiting the UV-mediated increase in ROS and malondialdehyde (MDA) levels in human keratinocytes and fibroblasts [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The JNK, p38, and ERK are mainly included in the MAP-kinase pathway. The pathway is involved in cell proliferation, differentiation, stress adaptation, and apoptosis [ 34 ]. OSU-03012 also suppressed c-Jun NH2-terminal kinase/signal transducers and transcription activators, and MAPK pathways in multiple myeloma cells, according to Zhang and colleagues [ 35 ].…”
Section: Discussionmentioning
confidence: 99%